(untitled) (Bangladesh Agronomy Journal, 2015)
The experiment was conducted at research field of Agricultural Research Station, BARI, Comilla during November 2012 to June 2013 with a view to find out economic fertilizer dose for potato- hybrid maize relay cropping system. The potato variety BARI Alu-7 and the maize variety BARI Hybrid Maize-7 were used. Seven fertilizer combinations viz. T1= Farmers fertilizer dose of potato (FFDP) + without additional fertilizer for maize (WAFM), T2= FFDP + 100% N of recommended fertilizer dose of hybrid maize (RFDM), T3= FFDP + 100% N & 25% others of RFDM, T4= FFDP + 100% N & 50% others of RFDM, T5= Recommended fertilizer dose of potato (RFDP) +100% N of RFDM, T6= RFDP +100% N & 25% others of RFDM and T7= RFDP +100% N & 50% others of RFDM were tested on potato-hybrid maize relay cropping system. Farmers fertilizer dose for potato was 504-162-309 kg ha-1 NPK. Recommended fertilizer dose for potato and hybrid maize was 198-44-194-24-6-1.2 kg ha-1 NPKSZnB and 255-55-140-40-6-2 kgha-1 NPKSZnB, respectively. The highest potato equivalent yield (37.80 t ha-1) and gross return (4,53,600 Tk. ha-1) were obtained from T3 treatment. But the maximum gross margin (Tk. 3,03,075 Tk. ha-1) was found from treatment T1 and the highest benefit cost ratio (3.14) was observed in T5 whichwas close to T1 (3.06) and T6 (3.0) .The results revealed that recommended fertilizer dose of potato and 100% N from recommended fertilizer dose of hybrid maize might be used for potato hybrid maize relay cropping system for getting higher economic return at Comilla region. Bangladesh Agron. J. 2014, 17(2): 9-13